NEW APPROACHES TO DIAGNOSTICS OF VESICOURETERAL REFLUX IN CHILDREN - A.V. Ryabtseva; S.P. Yatsyk; D.K. Fomin (Union of pediatricians of Russia, 2010)
Vesicoureteral reflux in children without diagnostics and correct treatment could result in chronic renal failure. This prognosis forces to look for new more informative methods of diagnostics. The authors of the article conducted research to assess the reliability of key methods - radionuclide and radiological methods. The results obtained indicate the need for a differentiated approach to each child and advisability of comprehensive examination of a child using various methods not only to identify the presence of reflux, but also its duration, intensity in order to select the right tactics of treating the patient. Key words: vesicoureteral reflux, diagnostics, dynamic nephroscintigraphy, radionuclide cystography, voiding cystography, children. (Pediatric Pharmacology. - 2010; 7(3):95-97)